The Spanish Civil War : A Very Short Introduction - Graham, Helen, 1959- (Oxford, New York Oxford University Press, 2005)
Amid the catastrophes of the twentieth century, the Spanish Civil War continues to exert a particular fascination. The Spanish Civil War: A Very Short Introduction provides a powerfully-written explanation of the war's complex origins and course, and explores its impact on a personal and an international scale.
Include Illustration, Glossary and Index
Keywords: Spain -- Civil War (Spain : 1936-1939)